Diabetic foot off loading and ulcer remission: Exploring surgical off-loading. Issue 6 (December 2021) - Ahluwalia, Raju; Maffulli, Nicola; Lázaro-Martínez, José L.; Kirketerp-Møller, Klaus; Reichert, Ines
Abstract: Introduction: Diabetic peripheral neuropathy leads to foot deformity, soft tissues damage, and gait imbalance, all of which can increase the mechanical stress imposed on the foot and give rise to Charcot neuroarthropathy. The current International Working Group of the Diabetic Foot International Guidelines on offloading focus on managing neuropathic foot ulcers related to pressure: only 2 of their 9 recommendations deal with surgical interventions. We assess the role of surgical techniques in off-loading to heal and possibly prevent diabetic foot ulceration. Methods: We systematically analysed published data from January 2000 to November 2020 to assess methods of surgical offloading and associated outcomes for the surgical reconstruction. We tried to identify healing, remission-rates, return to ambulation, complications and limitations. Results: Five discrete categories of surgical offloading are used in recalcitrant ulcers: 1. Lesser toe tenotomies; 2. Metatarsal head resection ± Achilles tendon release; 3. Hallux procedures; 4. Bony off-loading procedures in the form of exostectomy; and 5. Complex surgical foot reconstruction. Adjuvant modalities including surgically placed antibiotic delivery systems show promise, but further studies are required to clarify their role and effect on systemic antibiotic requirements. Conclusions and implications: Surgery is important to mechanically stabilise and harmonise the foot for long term off-loading and foot-protection. Surgery should not be reserved for recalcitrant cases only, but extended to ulcer prevention and remission. Further comparative studies will benefit surgical decision making to avoid recurrence and define time point when surgical off-loading could protect against irretrievable tissue loss/re-ulceration.